Piecing Memories, Connecting Lives: The (Inter)Textual Quilt in Phyllis Alesia Perry’s Stigmata - Kovalová, Karla (American & British Studies Annual, 2010)
The use of structural and thematic qualities of the quilt has given rise to a rich tradition in American women’s literature, reflecting the historical transformation of American women’s culture and/or suggesting alternative modes of perception. Using the quilt as a tool for textual analysis, this paper will explore Phyllis Alesia Perry’s Stigmata (1998), a debut novel describing three generations of black women bound by a shared legacy of slavery. Perry establishes herself in the tradition of black women’s writing, while creating in her work “an intertextual quilt” that challenges perceptions of American history.